Literary element order of Square Kufic in Malaysian modern paintings / Sarah Asyikin Abdul Rahim and Nor Azlin Hamidon - Abdul Rahim, Sarah Asyikin; Hamidon, Nor Azlin (Faculty of Art and Design, 2022)
The paper focuses on Square Kufic, a historical classification system for Arabic writing styles. The researchers expected a complete record of the Square Kufic inscriptions with the appearance of essential collections of symbols of the Muslim world. Religious inscriptions, such as Square Kufic, have been neglected or recorded inconsistently. While fundamentally defined by its geometric and angular features, there is no universally accepted norm or standardisation regarding the use of Square Kufic. This research aims to study the types of Kufic in Islamic civilization, explore the characteristics of Square Kufic, and analyse the structural formation of Square Kufic in the painting. This study is based on both primary and secondary data. A semi-structured interview and observation are used to get primary data, whereas secondary data includes references from books, papers, journals, and the internet. The study's outcomes indicate the Kufic calligraphy style's specific features result in more modifications than the conventional style. The artists consequently came up with various forms and patterns to adapt their artwork following the period's rules and societal expectations. Square Kufic no longer applies as fixed due to its distinctive dynamism. A wide range of writing styles has developed in various mediums, giving the structure its visual life and transforming it into a modern art form that communicates insights. Hopefully, this study will contribute to disseminating knowledge and understanding about the Square Kufic in Malaysia.